Pembuatan Film Pendek Allure Of Culture Dengan Teknik Edit Continuity Cutting - Alvia Kharismasari; Ilfa Nurdina Ridho; Natasya Yasmin Kinanti; Ahmad Chusyairi (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2020)
The short film Allure of Culture tells the story of the appeal of culture to the youngergeneration. Three teenagers from different cities with different languages, eachdifferent, and also each learning from each other. The film is set in the Banyuwangiarea. and has a lot of local cultural wisdom that is still preserved by the Banyuwangicommunity which attracts visitors, including teenagers. They will not forget theculture, now rarely use local languages, they do not want to forget local languages.The benefit of the short film Allure of Culture is to invite the Indonesian people tonot forget to keep preserving the culture of their respective regions. One of them stilluses local language everyday. Not only language, in this film also asked to remainrelated to culture, for example Banyuwangi the tradition of kebo-keboan. This filmuses the Continuity Cutting editing technique. The Continuity Cutting technique isa method of editing a film that contains an extension of two scenes that havecontinuity. The development method used is qualitative and quantitative methods.The conclusion obtained in this research is producing a film that aims to support theeducation in Banyuwangi for all of Indonesia, also invites Indonesian people,especially young people, to preserve local agriculture by using everyday languageand maintaining local wisdom.